1990
DOI: 10.1007/bf00548935
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose in yeast, stress protectant rather than reserve carbohydrate

Abstract: Trehalose and glycogen are generally regarded as the two main reserve carbohydrates in yeast. However, several lines of evidence suggest that trehalose does not primarily function as a reserve but as a highly efficient protecting agent to maintain structural integrity of the cytoplasm under environmental stress conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
292
0
10

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 501 publications
(309 citation statements)
references
References 38 publications
7
292
0
10
Order By: Relevance
“…Trehalose (α--glucopyranosyl α--glucopyranoside) is well known to act as a stress protectant in yeast and other organisms and displays potent protective effects against denaturation of proteins and other cellular components in itro [1,2]. In numerous studies a positive correlation has been observed between the trehalose level and stress resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trehalose (α--glucopyranosyl α--glucopyranoside) is well known to act as a stress protectant in yeast and other organisms and displays potent protective effects against denaturation of proteins and other cellular components in itro [1,2]. In numerous studies a positive correlation has been observed between the trehalose level and stress resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The function and the expression of the NTH2 Abbreviations used : PKA, cAMP-dependent protein kinase ; Nth1, neutral trehalase ; STRE, stress-responsive element. 1 To whom correspondence should be addressed (e-mail stefaan.wera!bio.kuleuven.ac.be). 2 Present address : Department of Biochemistry, University of Kentucky Medical Center, Lexington, KY 40536-0084, U.S.A.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, trehalose synthesis is induced in most of these organisms in response to a small set of specific environmental conditions. In particular, trehalose is accumulated in phases of nutrient starvation, desiccation, and after exposure to a mild heat shock (for reviews see Van Laere, 1989;Wiemken, 1990;Crowe et al, 1992). It has been suggested, therefore, that trehalose plays a role as a stabiliser of cellular structures under stress conditions (Keller et al, 1982;Crowe et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of trehalost correlates with an mcredqe m thcrmotolcrance [ 1 I], suggesting that trehalosc IS a protective substance m yeast [12,13]. Enzyme measurements in extracts prepared by disruption of cells with glass beads at 4'C hdve C~~rrcr/~c,trkrlre urlrircrr A Wlcmkcn, Botatu~chc~ Instltul, Hcbclstrassc I, CH-405G Uascl, SwltzcrLmd fax (41) (61) 261 5318 yielded the surprising result that not only trehalose-Gphosphate synthase but also neutral trehalase actlvlty rapldly Increases upon heat shock, suggesting a high turn-over of trehalose during the heat shock [9] Considering the potential problems of the sampling procedure [8] mentioned above, we decided to reinvestigate the regulation of neutral trehalase under heat shock condltlons Here we report that the previously used extraction method [9] leads to artlficlally high actlvmes under heat shock condltlons apparently due to rapid phosphorylation during sampling.…”
Section: Introductionmentioning
confidence: 99%